Rule of law, common values and illiberal constitutionalism : Poland and Hungary within the European Union - Drinóczi, Tímea <<[HerausgeberIn]>> (Routledge, 2020)
Illiberal Constitutionalism and the European Rule of Law / Tímea Drinóczi, Agnieszka Bień-Kacała – The European values and the Rule of Law / Andrzej Madeja – Where the laws do not govern, there is no constitution' : on the relationship between the Rule of Law and Constitutionalism / Wojciech Włoch – The Rule of Law, Democracy and Human Rights in Hungary : tendencies from 1989 until 2019 / András Jakab and Eszter Bodná – The Rule of Law : the Hungarian Perspective / Tímea Drinóczi – The Rule of Law : the Polish perspective / Iwona Wróblewska – Rule of Law in Hungary. What can law and politics do? / Lóránt Csink – Safeguarding the European Union's core values : the EU Rule of Law Mission in Poland / Sylwia Majkowska-Szulc – Are the EU member states still masters of the treaties? The European Rule of Law Concept as a means of limiting national authorities / Agnieszka Grzelak – Illiberal legality / Tímea Drinóczi and Agnieszka Bień-Kacała.
Includes bibliographical references and index